Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1001/jamasurg.2022.5157
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of National Institutes of Health Research Funding for Women Surgeon-Scientists

Abstract: ImportanceWomen have made substantial advancements in academic surgery, but research funding disparities continue to hamper their progress, and current literature on the status of National Institutes of Health (NIH) funding awarded to women surgeon-scientists appears to be conflicting.ObjectiveTo examine gender-based differences in NIH funding awarded to surgeon-scientists by comparing total grant amounts awarded and the distribution of grants by gender and research type.Design, Setting, and ParticipantsThis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…8 Our findings are consistent with previously published findings that men and women surgeon-scientists have similar rates of converting NIH career development awards to R01 grants and similar numbers of R01 application attempts prior to success. 22 Despite the success of women surgeon-scientists, the number of women surgeon-scientists is still relatively small compared with the proportion of women academic surgeons. A prior study concluded that there is an overrepresentation of women surgeon-scientists compared with academic surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Our findings are consistent with previously published findings that men and women surgeon-scientists have similar rates of converting NIH career development awards to R01 grants and similar numbers of R01 application attempts prior to success. 22 Despite the success of women surgeon-scientists, the number of women surgeon-scientists is still relatively small compared with the proportion of women academic surgeons. A prior study concluded that there is an overrepresentation of women surgeon-scientists compared with academic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…This is a remarkable achievement that is not universal among the biomedical research workforce, where women and men biomedical scientists are of comparable age when obtaining their first R01 grant . Our findings are consistent with previously published findings that men and women surgeon-scientists have similar rates of converting NIH career development awards to R01 grants and similar numbers of R01 application attempts prior to success …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research reveals that access to research funding, despite some progress in the past decade, still varies substantively between women and men. [18][19][20][21][22] Women's scientific contributions are systematically less likely to be recognized, resulting in a gender gap in attribution. 23 Furthermore, women experience less sponsorship (the public commitment of a leader to support the career advancement of another individual), which is associated with visibility, credibility, and professional networking.…”
Section: Discussionmentioning
confidence: 99%
“…The factors associated with differences in academic productivity between men and women head and neck surgeons as their careers progress are substantial. Prior research reveals that access to research funding, despite some progress in the past decade, still varies substantively between women and men . Women’s scientific contributions are systematically less likely to be recognized, resulting in a gender gap in attribution .…”
Section: Discussionmentioning
confidence: 99%